Efisiensi Waktu Pengemasan Keripik Menggunakan Alat Pengemas Semi Otomatis Berbasis Internet of Things - Arif Suersa; Muhammad Rasid; Dwi Arnoldi (Bulletin of Community Engagement, 2024)
This research aims to improve the efficiency and quality of chip packaging by testing four main aspects: stepper motor speed, sensor errors, the effect of sealer temperature on packaging quality, and a comparison of semi-automatic and manual packaging times.  Stepper motor speed testing was conducted to find the optimal speed, which was found to be 300 RPM. At this speed, the average packaging time per product is 7.84 seconds with a total of 36 products packed in 5 minutes. Error testing on the sensors showed that the Ir Proximity and Ultrasonic (Plastic) sensors had a high accuracy of 86.7%, while the Ultrasonic (Chips) sensor had an accuracy of 80%. Sealer temperature testing showed an optimal temperature of 57.9°C to achieve the best packaging quality. High temperatures such as 112.1°C result in poor packaging quality. Comparison of packaging times showed that the semi-automated method with a 300 RPM motor was more efficient, producing an average of 36 products in 5 minutes compared to 16 products using the manual method. The results of this study show that the use of stepper motors at 300 RPM, high-accuracy sensors, proper sealer temperature settings, and semi-automated technology in the packaging process can improve the efficiency, quality, and consistency of chip packaging production.